Hambatan Komunikasi Karyawan Generasi Z dengan Karyawan Generasi Y dan Generasi X dalam Lingkungan Kerja: Penelitian - Zaldy Handi Aditia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
In a multigenerational work environment, communication is one of the most crucial aspects for the smooth running of company activities. However, differences in background, habits, and technology used between generations often create communication barriers. This study aims to identify and analyze communication barriers between Generation Z employees and Generation Y and Generation X employees. This study uses a qualitative method with a case study approach in several companies in Jakarta. Data were collected through in-depth interviews with 15 respondents consisting of Generation Z, Y, and X employees. The results of the study showed that communication barriers were influenced by differences in communication media preferences, differences in perspectives on work, and the language style used. This study concluded that effective communication can be achieved.